2017
DOI: 10.18632/oncotarget.16929
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphisms in IL-1R1 and IL-1R2 genes with IgA nephropathy in the Han Chinese population

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Moreover, no significant association was also found between rs2072472 and the risk of ankylosing spondylitis (Xia et al, ) and endometriosis (Chun et al, ). Previous study reported that rs3218977 was found to be associated with a 0.71‐fold decrease risk of IgA nephropathy in the dominant model (GA‐GG vs. AA) (Xie et al, ). A case‐control association study found that the SNP rs3218977 was associated with an increased risk of aggressive periodontitis in the additive model in the Japanese (Kamei et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, no significant association was also found between rs2072472 and the risk of ankylosing spondylitis (Xia et al, ) and endometriosis (Chun et al, ). Previous study reported that rs3218977 was found to be associated with a 0.71‐fold decrease risk of IgA nephropathy in the dominant model (GA‐GG vs. AA) (Xie et al, ). A case‐control association study found that the SNP rs3218977 was associated with an increased risk of aggressive periodontitis in the additive model in the Japanese (Kamei et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…However, association studies indicated that rs4851527 was associated with decreased risk of tuberculosis (Ren et al, ) and ankylosing spondylitis (Xia et al, ). No significant association was found between the two SNPs (rs3218896 and rs2072472) and risk of IgA nephropathy (Xie et al, ), tuberculosis (Ren et al, ), and breast cancer (Zuo et al, ). Moreover, no significant association was also found between rs2072472 and the risk of ankylosing spondylitis (Xia et al, ) and endometriosis (Chun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(Khoufache et al, ). Many studies reported that the IL1R2 as a protected factor can decrease the risk of many diseases, such as IgA nephropathy (Xie et al, ), Arthritis (Shimizu et al, ), and atherosclerosis (Pou et al, ). However, there were few researches about the IL1R2 genetic polymorphisms in previous studies, and no studies have been reported the genetic polymorphism of IL1R2 and HAPE risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research has uncovered the genetic polymorphisms of IL1R1 and IL1R2 associated with several diseases. Variants in IL1R1 and IL1R2 have been reported with regard to their influence on knee osteoarthritis risk and IgA nephropathy in the Chinese Han population . Both IL1R1 and IL1R2 are multifunctional cytokines in inflammatory biological processes, which is strongly associated with thyroid carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Variants in IL1R1 and IL1R2 have been reported with regard to their influence on knee osteoarthritis risk and IgA nephropathy in the Chinese Han population. [21][22][23] Both IL1R1 and IL1R2 are multifunctional cytokines in inflammatory biological processes, which is strongly associated with thyroid carcinogenesis. Their distinct roles in thyroid cancer development may actually be worthy of more attention.…”
Section: Introductionmentioning
confidence: 99%